Effect of phosphate supplementation on growth and extracellular enzyme production by some edible mushrooms - Kamal, Shwet; Upadhyay, R C; Ahlawat, O P; Singh, Manjit (Mushroom Research, 2012)
This research communication reports the effect of phosphate concentration on mycelial growth rate, production of lignolytic extracellular enzymes and substrate utilization by mushrooms. Four strains of three commercially important mushrooms viz., Agaricus bisporus (S-11), A. bisporus (U-3), Pleurotus florida (P-1) and Volvariella volvacea (OE-12), were taken for the study. Addition of inorganic phosphate invariably increased the mycelial growth rate, extracellular enzymes and protein production. The optimum concentration of the phosphate for mycelial growth was found to be 0.05%, 0.025% and 0.1% in A. bisporus, P. florida and V. volvacea, respectively. Addition of Phosphorus almost doubled mycelial biomass whereas enzyme assay increased 4-5 folds in the test strains. Further, in strains of A. bisporus, the total protein content also increased almost 4-5 times. In V. volvacea, the enzymes viz., lignin peroxidase, manganese dependent peroxidase and alkaline phosphatase could not be detected in control but were induced at 0.025% phosphate concentration implying the requirement of available phosphates for efficient utilization of the substrate.